ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA SELAMA PANDEMI COVID-19 DITINJAU DARI MINAT BELAJAR SISWA - Christin Elisabet Sihombing; Roslian Lubis; Nunik Ardiana (JURNAL MathEdu (Mathematic Education Journal), 2021)
The purpose of this study is to analysis students' mathematical reasoning ability during Covid -19 pandemic in terms of student interest in learning. Subject of the research is eighth grade students of SMP Negeri 5 Padangsidimpuan. The approach of the research used qualitative. Instrument of the research used test, close questionnaire, and interview. Data analysis includes data reduction, data presentation, and taking conclusion.The result of the research showsstudents' mathematical reasoning ability during Covid -19 pandemicis low category, 20% is high category, 20% is enough category, and 60% is low ability. The result of questionnaire concludes 60% students have low mathematical reasoning ability and low learning interest because don’t like mathematical subject, 20% students have average mathematical reasoning ability and average learning interest becausethey will like mathematical subject if mathematical teacher teach the subject in fun away, and 20% students have high mathematical reasoning ability and high learning interest because they like mathematical subjectand always challenged with math problems.